Effects of MgCl2 on the gasification kinetics of petroleum coke. Issue 6 (19th March 2019) - Tian, Wei; Liang, Rongzhen; Yan, Fusheng
ABSTRACT: MgCl2 is used as catalysts for petroleum coke-CO2 gasification. The effect of catalyst addition amount and gasification temperature on petroleum coke-CO2 gasification is studied by using thermogravimetric analyzer. It is shown that magnesium chloride has a catalytic effect on petroleum coke gasification. At the same temperature, the time required for complete gasification of petroleum coke decreases with the increase of catalyst dosage. There is a limit to the amount of catalyst added, and the best amount of magnesium chloride is 5%. The kinetics model of petroleum coke catalytic gasification is described by using the homogeneous model, the shrinkage model, and the Gaussian model, respectively. Compared with the gasification reaction activation energy calculated by the conversion method. It is shown that the shrinkage model can better describe the dynamic characteristics of petroleum coke catalytic gasification.